Development of n-MoO3@MoS2/p-Si heterostructure diode using pre-synthesized core@shell nanocomposite for efficient light harvesting detector application. (15th November 2021) - Gunasekaran, S.; Marnadu, R.; Thangaraju, D.; Chandrasekaran, J.; Hegazy, H.H.; Somaily, H.H.; Durairajan, A.; Valente, M.A.; Elango, M.; Minnam Reddy, Vasudeva Reddy
Abstract: Novel nanostructure formations like core-shell influence the sensing nature of the optoelectronic devices. In this report, transition metal oxides (TMOs) and transition metal dichalcogens (TMDCs) based sensing layer fabrication and their influence in photo sensing performances were analysed. The metastable h-MoO3, thermally stable α-MoO3, as synthesized MoS2 and combinational MoO3 @MoS2 core@shell nanocomposites are synthesized by co-precipitation method. Phase purity of synthesized particles was analysed with XRD. Vibration modes of the samples were confirmed with Raman spectroscopy. The morphology behaviours of MoO3 in different polymorphs due to annealing temperature namely prismatic like h-MoO3, layered rod like α-MoO3 and sphere like MoS2 decorated core@shell MoO3 @MoS2 were observed in the FE-SEM micrographs. The core@shell rod like structured was recorded with HRTEM. Further construction of photodiodes such as n-(h-MoO3 )/p-Si, n-(α-MoO3 )/p-Si, n-MoS2 /p-Si and n-MoO3 @MoS2 /p-Si by employing solution processed method with pre-synthesized particles were discussed in detail. The current-voltage (I–V) characteristics and photo sensing parameters of detector are compared. From the experimental result, n-MoO3 @MoS2 /p-Si has better photosensitivity (PS ) of 21678.6 (%) and the specific detectivity (D*) of 5.813 × 10 10 Jones. Graphical abstract: Image 1 Highlights: Novel n-MoO3 @MoS2 /p-Si heterostructure diode has been facilely developed. Structural and vibrational studied confirm the fabrication of n-MoO3 @MoS2 system. MoS2 decorated core@shell MoO3 @MoS2 was observed in the FE-SEM micrographs and core@shell rod like structured were recorded with HRTEM. The development of photodiodes such as n-(h-MoO3 )/p-Si, n-(α-MoO3 )/p-Si, n-MoS2 /p-Si and n-MoO3 @MoS2 /p-Si has been done. n-MoO3 @MoS2 /p-Si shows (PS ) of 18659 (%) and the (D*) of 5.813 × 10 10 Jones.